Dynamic Acquisition and Loss of Dual-Obligate Symbionts in the Plant-Sap-Feeding Adelgidae (Hemiptera: Sternorrhyncha: Aphidoidea) - von Dohlen, Carol D.; Spaulding, Usha; Patch, Kistie B.; Weglarz, Kathryn M.; Foottit, Robert G.; Havill, Nathan P.; Burke, Gaelen R. (Frontiers in Microbiology, 2017)
Sap-sucking insects typically engage in obligate relationships with symbiotic bacteria that play nutritional roles in synthesizing nutrients unavailable or in scarce supply from the plant-sap diets of their hosts. Adelgids are sap-sucking insects with complex life cycles that involve alternation between conifer tree species. While all adelgid species feed on spruce during the sexual phase of their life cycle, each adelgid species belongs to a major lineage that feeds on a distinct genus of conifers as their alternate host. Previous work on adelgid symbionts had discovered pairs of symbionts within each host species, and unusual diversity across the insect family, but left several open questions regarding the status of bacterial associates. Here, we explored the consistency of symbionts within and across adelgid lineages, and sought evidence for facultative vs. obligate symbiont status. Representative species were surveyed for symbionts using 16S ribosomal DNA gene sequencing, confirming that different symbiont pairs were consistently present within each major adelgid lineage. Several approaches were used to establish whether symbionts exhibited characteristics of long-term, obligate mutualists. Patterns of symbiont presence across adelgid species and diversification with host insects suggested obligate relationships. Fluorescent in situ hybridization and electron microscopy localized symbionts to bacteriocyte cells within the bacteriome of each species (with one previously known exception), and detection of symbionts in eggs indicated their vertical transmission. Common characteristics of long-term obligate symbionts, such as nucleotide compositional bias and pleomorphic symbiont cell shape were also observed. Superimposing microbial symbionts on the adelgid phylogeny revealed a dynamic pattern of symbiont gains and losses over a relatively short period of time compared to other symbionts associated with sap-sucking insects, with each adelgid species possessing an older, “senior” symbiont and a younger “junior” symbiont. A hypothesis relating adelgid life cycles to relaxed constraints on symbionts is proposed, with the degradation of senior symbionts and repeated acquisition of more junior symbionts creating opportunities for repeated colonization of new alternate-conifer hosts by adelgids.